Individual, Service, and Neighborhood Predictors of Aggression Among Persons With Mental Disorders - Seto, Michael C. (Criminal justice and behavior, 2018)
We examined the predictive validity of individual, service, and neighborhood factors for aggression by 1,491 forensic clients found Not Criminally Responsible on account of Mental Disorder (NCRMD), under the jurisdiction of a Review Board, and thus subject to supervision conditions. Younger patient age and personality disorder diagnosis were associated with both clinically documented aggression and recidivism. Medication adherence was related to clinically documented aggression, but not criminal recidivism. Number of reports from an institution (possibly reflecting assessor or institutional experience with NCRMD assessments) did not predict clinically documented aggression, but more comprehensive risk reports were associated with fewer such clinical incidents. More community mental health resources within a 45-min drive of an individual’s residence were associated with less recidivism, but not less clinically documented aggression. We conclude that extra-individual factors are related to aggression, the neighborhood to which forensic clients return matters, and effects can differ for criminal recidivism versus clinically documented aggression.